Analisis Metode Penelitian Eksperimen pada Pembelajaran IPA di Tingkat Sekolah Menengah Pertama (SMP) - Rahayu Laelandi; Babang Robandi (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
Various types of educational devices that are used as a support for the creation of a good education are certainly important. One of them is using an effective method to provide a concept to students optimally. This study aims to analyze how high and important the influence of the experimental method on science subjects at the junior high school. The method used is a qualitative research method with a mini survey method on 47 samples consisting of junior high school students, high school students, college students, and alumni students as well as a literature study method (library study) which is carried out by screening electronic books (e-books) and e- journals. The results showed that 94% of experimental research methods were effectively used and 6% were not effectively used in the science learning process. The effectiveness of this method is that students can prove that an accepted concept is in accordance with the given theory and students can hone their psychomotor abilities. The weakness of this method is that it can be seen from the inadequate infrastructure, the ability of teachers, controlling students, and the selection of practicum materials.